Noise Sources in Turbulent Shear Flows: Fundamentals and Applications - Camussi, Roberto; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer, 2013)
The articles in this volume present the state-of-the-art in noise prediction, modeling and measurement. The articles are partially based on class notes provided during the course `Noise sources in turbulent shear flows', given at CISM on April 2011. The first part contains general concepts of aero acoustics, including vortex sound theory and acoustic analogies, in the second part particular emphasis is put into arguments of interest for engineers and relevant for aircraft design: jet noise, airfoil broadband noise, boundary layer noise (including interior noise and its control) and the concept of noise sources, their theoretical modeling and identification in turbulent lows. All these arguments are treated extensively with the inclusion of many practical examples and references to engineering applications.
Fundamentals: Introduction to aero acoustics and self-sustained oscillations of internal flows -- Sound radiation by moving surfaces and the Greens functions techniques -- Applications: Jet noise -- Analysis techniques for aero acoustics: noise source identification -- Broadband noise from lifting surfaces: analytical modeling and experimental validation -- Boundary layer noise: generation mechanisms -- Interior noise radiation and control.
Keywords: Engineering; Vibration; Hydraulic engineering; Astronautics; Engineering; Engineering Fluid Dynamics; Aerospace Technology and Astronautics; Vibration, Dynamical Systems, Control